The Rice Aspartyl-tRNA Synthetase YLC3 Regulates Amino Acid Homeostasis and Chloroplast Development Under Low Temperature - Liu, Hongjia; Gong, Xue; Deng, Hui; Tan, Jinjuan; Sun, Yanqing; Wang, Fang; Wu, Wenjuan; Zhou, Zhongjing; Xu, Rumeng; He, Haiyan; Lo, Clive (Frontiers in Plant Science, 2022)
Aminoacyl tRNA synthetases primarily function to attach specific amino acids to the corresponding tRNAs during protein translation. However, their roles in regulating plant growth and development still remain elusive. Here we reported a rice thermo-sensitive mutant yellow leaf chlorosis3 (ylc3) with reduced chlorophyll content, altered thylakoid structure, and substantially elevated levels of free aspartate, asparagine and glutamine in leaves under low temperature condition. Map-based cloning identified that YLC3 encodes an aspartyl-tRNA synthetase which is localized in cytosol and mitochondria. In addition, quantitative proteomics analysis revealed that both nuclear and chloroplast-encoded thylakoid proteins were significantly down-regulated in the mutant. On the other hand, proteins involved in amino acid metabolism and the process of protein synthesis were up-regulated in ylc3, particularly for key enzymes that convert aspartate to asparagine. Moreover, uncharged tRNA-Asp accumulation and phosphorylation of the translation initiation factor eIF2α was detected in the mutant, suggesting that YLC3 regulates the homeostasis of amino acid metabolism and chloroplast thylakoid development through modulation of processes during protein synthesis.